An analysis of trade of the eurasian economic union - (:unkn) unknown (IGI Global, 2018)
After the creation of the Eurasian Economic Union in 2015, the Customs Union and the Common Economic Space between Russia, Belarus, and Kazakhstan represented two of the most important regional integration projects launched in the post-Soviet era. However, even though institutions, customs unions, and a common economic space have been established, it has become a matter of debate whether this union is effective in developing trade between the member countries. Russia has enormous power in terms of its share of the trade within the EEU. This shows Russia has economic dominance in the union. This is also the subject of debate about whether the union's members, except Russia, benefit from the customs union. In this chapter, the answers to these questions have been investigated by evaluating the commercial activities and macroeconomic variables of the member countries of the Eurasian Economic Union. © 2018, IGI Global.